Estudo de controladores aplicados a inversores para UPS com operação ilhada - Guillardi Júnior, Hildo [UNESP] (2013)
This dissertation presents the design, simulation and testing of the prototype os the stage of output of a UPS (Uninterruptible Power Supply) single-phase with voltage equal to 127V and three-phase with voltage equal to 127V and three-phase with voltage equal to 220/127V four-wired, both with 60Hz and nominal power of 1kVA to use in inslanded mode. The validation of the methodology of the project was realized first in simulation, and subsequently, experimentally using different kinds different kinds of loads typically found in electrical installations and, different kinds of classical controllers: PI (Proportional Integrative Controller), Resonant and composition of both. The testing has consisted of 2 stages: steady state and transitory state, in the first stage, it has been measured the RMS (Root Mean Square) value and THD (Total Harmonic Distortion) of the voltage of the output and, in the second stage, the behavior in relation to the loads step in and step out, highlighting the stability of the control. The standardized procedures of the test have been applied in the two stage and the results were compared to the requirements of the applicable standards to this kind of power converter. It has been used a fixed point DSP (Digital Signal Processing) as a device of control, which was responsible for the calculation of the control algorithm and for the signal sampling of voltages and currents of the inverter; being measured its processing capacity in relation to the conservation of power quality and the signal frequency of output. The project has indicated the necessary of the multi-loop control, i.e, voltage plus current controller, due to the instability generated in its transfer function when supplying non-resistive loads. It has been also demonstrated in simulation, the possibility of the power interface works in others functionalities: Rectifier with Power Factor Correction (to battery recharge), Current Source Inverter...